Από την Ιστορία του Κόσμου στην Παγκόσμια Ιστορία ή από τον Ηρόδοτο στη μεγάλη απόκλιση - ΓΚΕΚΑΣ ΑΘΑΝΑΣΙΟΣ (Μνήμων, 2011)
This review essay outlines the two major approaches (through connections and comparisons) to the emerging field of Global History. The essay first summarizes recent historiographical developments that challenge and deconstruct Eurocentric periodisations of history. The essay then moves on to the discussion of the ‘great divergence’ between Asia and Europe; divergence in living standards, productive capabilities and ultimately geopolitical power that became more evident in the nineteenth century and continued to grow during the twentieth. An example of a Global History of cotton textiles is provided before concluding with some consequences of this historiographical trend (that some claim goes back to Herodotus) for the writing and interpretation of modern history. The essay surveys mostly works of Global Economic History and histories of globalization, highlighting the need of historians to respond to the challenges and opportunities of a globalizing world.